Adaptation as Means of Revising Gender Relations in Brian Friel’s A Month in the Country - Bach, Anikó (FOCUS: Papers in English Literary and Cultural Studies, 2012)
The aim of the present paper is to investigate Brian Friel’s A Month in the Country, in which the Irish writer refocuses attention to enhance the psychological nature of the drama and to allow space to the female voice that is given less emphasis in the original. To reveal the differences between Turgenev’s play and the adapted version of it, I will try to answer the question of to what extent the changes introduced by Friel contribute to the debates on gender relations in contemporary Irish society.